Antioxidant and Radical Scavenging Activities of Capsules of Caper (Capparis spinosa) - Nadaroglu, Hayrunnisa; Demir, Nazan; Demir, Yasar (Asian Journal of Chemistry, 2010)
There is more and more interest in caper (Capparis spinosa) in recent years as it has different areas to be applied especially within the food and cosmetic world. This study evaluated the in vitro antioxidant activity of water and ethanol extracts of capsules of caper (Capparis spinosa). The antioxidant properties of the caper were evaluated in vitro by antioxidant assays such as 2-azino-bis(3-ethylbenzthiazoline-6- sulfonic acid) (ABTS) radical scavenging, 1,1-diphenyl-2-picryl-hydrazyl free radical (DPPH•) scavenging, total antioxidant activity by ferric thiocyanate method, total reductive capability using the potassium ferricyanide reduction method, superoxide anion radical scavenging and metal chelating activities. a-Tocopherol, butylated hydroxyanisole (BHA) and butylated hydroxytoluene (BHT) were used as the reference antioxidant compounds. The concentration of 10, 30 and 50 μg/mL of water and ethanol extracts of caper showed 95.9, 96.4, 97.0, 97.04, 97.4, 94.8 % inhibition on peroxidation of linoleic acid emulsion, respectively. On the other hand, 30 μg/mL of standard antioxidant such as a-tocopherol indicated an inhibition of 88.1 % on peroxidation of linoleic acid emulsion. In addition capper is an effective ABTS• + scavenging, DPPH• scavenging, superoxide anion radical scavenging, total reducing power and metal chelating on ferrous ions activities.